Mitochondrial haplogroup B4 may be a protective factor to oral lichen planus susceptibility in Chinese. (17th February 2013) - Wu, D; Cheng, S; Chen, X; Sun, M; Wang, G; Fu, S; Dong, G; Wang, L; Wu, Y
<x xml:space="preserve">Abstract</x> Objective Oral lichen planus (OLP) is a common inflammatory disorder with a higher prevalence among women than men. The pathogenesis of OLP is still unclear, and its heredity is not well characterized. Maternal inheritance of mitochondrial DNA (mtDNA) indicates its importance in human ethnic group classification as well disease susceptibility. So, this study was conducted to find whether mtDNA haplogroup associates with OLP susceptibility in Chinese, and determine the influence of C‐stretch structure of mtDNA on OLP susceptibility. Subjects and methods We sequenced three hypervariable regions of mtDNA from 242 patients with OLP and 237 healthy controls. The association between mtDNA haplogroups and OLP is tested by chi‐square test. Results Seventeen kinds of haplogroups were identified, and the frequency of haplogroup B4 was significantly higher in control group than that of the OLP group (P = 0.013, OR=0.429). In female samples, B4 declared even more significance (P = 0.003, OR=0.296). Meanwhile, the haplotypes of C‐stretch in mtDNA did not have any significant difference between case‐control groups. Conclusions Mitochondrial DNA haplogroup B4 might have a protective effect to OLP, and its protective effect resides predominantly in women. However, the association between C‐stretch haplotype and OLP susceptibility still needs more patients for evaluation.